Steam Turbine Performance Analysis Based on Operational Parameter Variation: Analisis Kinerja Turbin Uap Berdasarkan Variasi Parameter Operasional - Luthfi Frans Setiawan; .A’rasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2026)
This study analyzes the performance of a steam turbine in relation to operational parameters within a power generation system. General Background: Steam turbines play a critical role in converting thermal energy into mechanical energy in power plants. Specific Background: Turbine performance is influenced by parameters such as steam flow rate, pressure, and blade configuration, which determine efficiency and output power. Knowledge Gap: Previous studies have examined turbine performance, yet limited attention has been given to detailed evaluation under specific operational conditions in practical systems. Aims: This research aims to evaluate the performance characteristics of a steam turbine by analyzing efficiency and operational parameters. Results: The findings show that variations in steam flow and operational conditions produce measurable differences in turbine efficiency and output, with certain conditions yielding optimal performance. Novelty: The study provides a focused evaluation of turbine performance using real or simulated operational parameters within a controlled framework. Implications: The results offer practical insights for optimizing turbine operation to achieve better energy conversion in power plant systems. Keywords: Steam Turbine, Performance Analysis, Efficiency, Power Plant, Energy Conversion Key Findings Highlights Operational parameters determine variations in output and system behavior Specific conditions yield peak operational performance during evaluation Measured data shows consistent patterns across tested scenarios